2006
DOI: 10.1038/sj.ejcn.1602568
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum minerals with body mass index in adult women

Abstract: Objective: This cross-sectional study evaluated the association between serum minerals and body mass index in adult women. Methods: One hundred and eighteen adult women were recruited by written advertisement from outpatient clinics or a health promotion center at a university hospital. Serum calcium, magnesium, copper and zinc were measured by an automatic analytical instrument and body mass index was calculated from height and weight. Results: Serum magnesium was inversely associated with body mass index (b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…It has also been suggested that differences in BMI could explain the lower serum zinc concentrations in women than in men. Although BMI was higher in men than in women, our results did not evidence any differences in serum zinc concentration according to BMI in agreement with some previous reports (Hashim et al, 1996;Benes et al, 2005;Song et al, 2007). Our results highlighted smoking and education as other significant determinants of serum zinc levels only in women.…”
Section: Discussionsupporting
confidence: 82%
“…It has also been suggested that differences in BMI could explain the lower serum zinc concentrations in women than in men. Although BMI was higher in men than in women, our results did not evidence any differences in serum zinc concentration according to BMI in agreement with some previous reports (Hashim et al, 1996;Benes et al, 2005;Song et al, 2007). Our results highlighted smoking and education as other significant determinants of serum zinc levels only in women.…”
Section: Discussionsupporting
confidence: 82%
“…27 hypoMagneseMia and loW-grade chronic inflaMMation The literature has shown that the diet of obese individuals has reduced magnesium content, which is a nutritional problem of great relevance. 28,29 Huang et al 30 and Song et al 31 found that dietary intake of magnesium is inversely proportional to body mass index, waist circumference, and body fat percentage.…”
Section: Metabolic and Physiological Aspects Of Magnesiummentioning
confidence: 99%
“…Conversely, other studies demonstrated an inverse correlation between serum Mg concentration and BMI 39,40 . a possible explanation of these findings is that they used serum Mg instead of daily Mg dietary intake.…”
Section: Anthropometric and Biochemical Measurementsmentioning
confidence: 92%